Fractures of metacarpal bone: evaluation of functional outcome of open reduction and internal fixation with mini locking plate: a hospital based study - Kandasamy, Arumugam A.; Pheroz, Mozammil; Kumar, Arvind; Krishna, L. G.; Jain, Ankit; Grower, Rahul (International Journal of Research in Orthopaedics, 2019)
Background: Metacarpal bones fracture is very common. Management of metacarpal fractures varies from conservative to percutaneous pinning to various surgical methods. We endeavour to evaluate the functional outcome of metacarpal fractures in patients managed with open reduction and internal fixation with mini locking plate. Methods: A total of 32 patients with extra-articular metacarpal bones fracture were recruited for the study. After open reduction the fractures were fixed with the mini locking plate, postoperative day 3, plaster removed and active and passive exercises started. The Michigan hand score was used for functional evaluation, grip strength, visual analogue scale score, range of motion evaluated at follow up till six months. Results: All the 32 patients achieved union, 31 had full union at 6 weeks whereas 1 patient has delayed union. The Michigan hand outcome questionnaire score of 97.5 % at 6 months in all 32 patients. A total of 5 out of 32 patients had complications, the most common being finger stiffness followed by superficial infection and delayed union. Conclusions: We concluded that metacarpal plating with mini locking plate is a good option to achieve and maintain a rigid fixation and this method produces a better outcome in unstable fractures of metacarpal bones.